Effect of organic and inorganic fertilization on the growth and yield of Gossypium hirsutum L. in Ecuador - Mera, Julio; Zambrano, Freddy; García, Marina; León, Rolando; Peñarrieta, Soraya; Sánchez-Urdaneta, Adriana (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2025)
The cultivation of cotton (Gossypium hirsutum L.) has a significant impact on the global economic and agricultural sectors, with its productivity being closely linked to nutrient management and the sustainability of the production system. The objective of this study was to evaluate the effect of organic and inorganic fertilization on the growth and yield of G. hirsutum in Ecuador. A completely randomized block design was used with a 2×4×2 factorial arrangement, which included two nitrogen sources (organic matter and urea), four nitrogen fertilization rates (50, 100, 150, and 200 kg N.ha-1), and the presence or absence of efficient microorganisms (EM). Phenological, morphometric, and yield-related variables were measured, along with foliar concentrations of N, P, and K. The results indicated that urea fertilization promoted greater vegetative growth and yield, while organic matter enhanced foliar potassium uptake. The application of efficient microorganisms (EM) did not produce statistically significant differences compared to the control treatment across all evaluated variables, as it significantly increased yield. Moreover, the interaction between nitrogen sources and fertilization rates showed that the combination of 150 kg N.ha-1 with EM optimized production. Inorganic fertilization with urea maximized cotton productivity, while organic matter contributed to a more sustainable production system, promoting sustainable agriculture.